(untitled) (The Himalayan Geographers, 2025)
In the recent decade, rapid urbanization and population growth at an alarming rate in Pokhara Metropolitan City have exposed it to multiple hazards. Multi-hazards study addressed several hazards, and identifying risk became essential for urban planning and preparedness. This study examined the spatial and temporal trends of multi-hazards (urban fire, flood, landslides, forest fire, and earthquake) incidents between 2018 to 2024, in ward-wise, monthly, and seasonal terms through a quantitative approach using ArcGIS for hotspots, R language for trend visualizations, and Chi-Square to measure significance in PMC. The findings reveal fire-related incidents dominating, while earth and water-related hazards are slightly lower. Spatial mapping highlights wards (17,6, 18, 24, 25) located in the northwestern region highly concentrated hazard zones. Temporal analysis indicates, April and July months peaked the incident counts, and the spring season, with moderate correlation (R2=0.4189), generates more incidents. Chi-square (X2 = 59.15, df = 18, α = 0.05) confirms the significance of season in the frequency of hazards. Overall, hazards distribution within PMC is uneven across wards, indicating a temporal pattern for incident occurrences. The findings offer insights for local government and stakeholders for interventions on focusing preparedness and hazard analysis.